Hiding texts in HTML pages - Aisha Siddeq Shaheen (College of Education for Pure Sciences, 2013)
Abstract: In this research the protection techniques are developed by using hiding in HTML pages which is suitable for ease of use on the other hand, the pages written in HTML, distributed largely on the Internet, so there is the possibility that the revealed contacts used for HTML pages is difficult, inspite of used techniques for network monitoring. Eight methods was applied in the concealment of which match the colors (Color matching) and property size (Size Attribute) and the use of labeling of (JavaScript) and the use of marking (CSS) and has been proposed other modalities of hiding are the property (Hover) and the link attribute (Link) and the property of field hidden (Hidden Field) and the replacement property (Alternate). Has also been used: Java script, CSS,HTML development environment in Dream Weaver8 for application of this research. خـص: